Radiation activated photodynamic therapy (radioPDT) induces lipid peroxidation and vascular mediated tumor regression of prostate cancer - Abul Kalam Azad; Deepak Dinakaran; Ronald B. Moore (Scientific Reports)
Abstract Photodynamic therapy (PDT) represents a promising cancer treatment strategy, leveraging external light sources to activate photosensitizers, which in turn generate reactive oxygen species (ROS) to target and destroy tumor cells. However, PDT’s efficacy has traditionally been limited to surface tumors due to limited light penetration through deep tissue structures requiring complex fiber optic delivery. Recent advancements have introduced nanoscintillators as an internal light source for photosensitizers, triggered by targeted X-ray radiation, thus extending the applicability of PDT to deep-seated tumors. While the in vitro tumor cell killing mechanisms of PDT have been extensively documented, comprehensive in vivo studies elucidating the mechanisms underlying radiation-activated photodynamic therapy (radioPDT) remain limited. In this study, we demonstrated that protoporphyrin IX-based radioPDT augments ROS generation, leading to PC3 prostate tumor cell killing in vivo, impeding tumor growth. ROS production led to a reduction in tumor vascular density with corresponding intratumoral hypoxia, while tumor vascular maturity remained unaffected. These results shed light on the multifaceted effects of radioPDT on the tumor microenvironment, emphasizing the potential for synergistic radiotherapeutic strategies in cancer treatment.